The Role of Organizational Justice in Reducing Job Slack: An Analytical Study in the General Directorate of Education in Nineveh Governorate - Ghassan Talal Najm Abdullah (Academia Open, 2026)
General Background: Organizational justice has increasingly been recognized as a fundamental organizational value shaping employee attitudes and behavioral responses within modern institutions. Specific Background: In public sector organizations, job slack represents a persistent behavioral problem characterized by reduced effort, low motivation, and diminished engagement, often associated with perceptions of unfair treatment. Knowledge Gap: Despite extensive discussion of organizational justice, limited empirical studies integrate its distributive, procedural, and interactional dimensions in explaining job slack within educational administrative institutions. Aims: This study aims to measure and analyze the relationship and role of organizational justice dimensions in reducing job slack among employees of the General Directorate of Education in Nineveh Governorate. Results: Using a descriptive-analytical approach with questionnaire data from 75 employees and statistical analysis via SPSS, findings reveal high levels of perceived organizational justice and job slack awareness, alongside a significant correlation (0.615) between the variables. Organizational justice explains 52% of variance in job slack, with procedural justice showing the strongest contribution compared to distributive and interactional justice. Novelty: The study proposes an integrated analytical framework linking multiple organizational justice dimensions simultaneously to job slack mechanisms within a public education context. Implications: The findings support adopting fairness-based administrative policies, transparent procedures, and equitable resource distribution to reduce disengagement behaviors and strengthen organizational commitment, providing practical guidance for public sector management and organizational behavior research. Highlights:• Organizational Fairness Dimensions Show Strong Statistical Association With Reduced Disengagement Behaviors.• Procedural Mechanisms Demonstrate the Highest Contribution Among Examined Organizational Practices.• Integrated Analytical Modeling Explains Substantial Variance in Employee Reduced-Effort Patterns. Keywords: Organizational Justice, Job Slack, Procedural Justice, Distributive Justice, Interactional Justice